AB0720 Performance of Referral Parameters of Patients with Chronic Back Pain Included in the Spondyloarthritis Caught Early Cohort (SPACE). (10th June 2014) - Pellegrom, S.; de Hooge, M.; Huizinga, T.; van der Heijde, D.; van Gaalen, F.
Abstract : Background: A recent study in Dutch primary care shows that axial spondyloarthritis (axSpA) is underdiagnosed1. A possible reason is that the effectiveness of referral parameters recommended by Dutch GP guidelines is not known. Objectives: To examine the referral parameters to the rheumatologist of patients included in the SPondyloArthritis Caught Early (SPACE) cohort and the extent to which they are associated with axSpA. Methods: Referral letters to rheumatologists for patients with chronic back pain (≥3 months, ≤2 years, onset ≤45 years) included in the SPACE cohort were used. Referral parameters analysed were the red-flags mentioned in the current back pain guideline from the Dutch GP association (NHG), features from the Assessment of Spondyloarthritis international Society (ASAS) inflammatory back pain (IBP) criteria, and the SpA features in the ASAS axSpA criteria. Arthralgia and myalgia were mentioned often and were added as referral parameters. AxSpA was defined as meeting ASAS classification criteria for axSpA Results: Clinical and referral data was available for 204 patients, 75 patients had axSpA (36.8%) and 129 patients had no axSpA (63.2%). 155 patients (75.9%) were referred by GPs, 15 patients (7.4%) by orthopaedist and 34 patients (16.7%) by other specialists. Mentioning in the referral letter of Improvement with exercise (OR 3.0; 95%CI 1.1-8.1), family history of SpA (OR 5.1; 95%CI 1.9-13.9) and a positive HLA-B27 (OR 12.2; 95%CI 3.9-37.1) were associated with axSpA. Arthralgia was negatively associated with axSpA (OR 0.4; 95%C I0.2-0.8). All ASAS axSpA features available at baseline in the SPACE cohort were found more often than in the referral letter see table. Conclusions: Most of the parameters mentioned in referral letters were not associated with axSpA. AxSpA features present in patients were often not mentioned in referral letters. To improve efficiency of referrals, physicians should be made more aware of SpA features. References: Weel A AC&R 2013 Sep 19 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3367